Diversity of the Gut Microbiota in Dihydrotestosterone-Induced PCOS Rats and the Pharmacologic Effects of Diane-35, Probiotics, and Berberine - Zhang, Feifei; Ma, Tong; Cui, Peng; Tamadon, Amin; He, Shan; Huo, Chuanbing; Yierfulati, Gulinazi; Xu, Xiaoqing; Hu, Wei; Li, Xin; Shao, Linus R.; Guo, Hongwei; et al. (Frontiers in Microbiology, 2019)
Polycystic ovary syndrome (PCOS) is a frequent endocrine and metabolic syndrome in reproductive-age women. Recently, emerging evidence has shown the close relationship between gut microbiota and metabolic diseases such as obesity, type 2 diabetes, and PCOS. In the present study, we established dihydrotestosterone (DHT)-induced PCOS rats and used Illumina MiSeq sequencing to examine the composition, richness, and abundance of the gut microbiota in PCOS, we compared the effects of three PCOS treatments – Diane-35 (estrogen and progesterone), probiotics, and berberine. The DHT-induced rats showed constant estrous cycles, the loss of mature ovarian follicles, insulin resistance and obesity. The reproductive and metabolic functions in the PCOS rats were improved by treatment with Diane-35 and probiotics. Diane-35 and probiotics could restore the diversity and abundance of the gut microbiota, the recovery of gut microbiota disorders improved the reproductive function in PCOS-like rats. However, berberine drastically reduced the species diversity and amount of intestinal flora and showed no improvement in PCOS. The findings of this study will help us to better understand the influence of the gut microbiota in the metabolic and reproductive alterations in PCOS, also suggest opportunities for future personal dietary guidance for PCOS.